Kajian Literatur Ilmu Faraidh dalam Pembelajaran Matematika - Syarqiyah, Rosyidatus; Faradiba, Surya Sari (Mandalika Mathematics and Educations Journal, 2025)
This study aims to examine the integration of fraction and division concepts in mathematics with the Islamic science of faraidh. The method used is a systematic literature review (SLR) consisting of five stages: formulating the research question, identifying relevant articles, assessing study quality, summarizing evidence, and interpreting findings. Article searches were conducted through Google Scholar using the keywords “integration of faraidh and fractions” and “integrasi ilmu faraidh dan pecahan,” with a publication range from 2020 to 2025. From 74 articles found, 10 met the eligibility criteria and were analyzed in depth. The findings show that inheritance distribution in faraidh is closely related to the concepts of fractions, division operations, least common multiples (LCM), and the 'aul method. These mathematical concepts are essential for understanding the inheritance portions mentioned in the Qur'an and for ensuring fair and proportional calculations. This integration not only strengthens students' numerical competencies but also builds spiritual understanding of justice in inheritance distribution according to Islamic law. Therefore, mathematics instruction that incorporates fiqh-based faraidh values is highly relevant to be developed in Islamic education.